Supported employment for people with severe mental illness: Systematic review and meta-analysis of the international evidence. (July 2016) - Modini, Matthew; Tan, Leona; Brinchmann, Beate; Wang, Min-Jung; Killackey, Eoin; Glozier, Nicholas; Mykletun, Arnstein; Harvey, Samuel B.
Abstract : Background: Individual placement and support (IPS) is a vocational rehabilitation programme that was developed in the USA to improve employment outcomes for people with severe mental illness. Its ability to be generalised to other countries and its effectiveness in varying economic conditions remains to be ascertained. Aims: To investigate whether IPS is effective across international settings and in different economic conditions. Method: A systematic review and meta-analysis of randomised controlled trials comparing IPS with traditional vocational services was undertaken; 17 studies, as well as 2 follow-up studies, were included. Meta-regressions were carried out to examine whether IPS effectiveness varied according to geographic location, unemployment rates or gross domestic product (GDP) growth. Results: The overall pooled risk ratio for competitive employment using IPS compared with traditional vocational rehabilitation was 2.40 (95% CI 1.99–2.90). Meta-regressions indicated that neither geographic area nor unemployment rates affected the overall effectiveness of IPS. Even when a country's GDP growth was less than 2% IPS was significantly more effective than traditional vocational training, and its benefits remained evident over 2 years. Conclusions: Individual placement and support is an effective intervention across a variety of settings and economic conditions and is more than twice as likely to lead to competitive employment when compared with traditional vocational rehabilitation.